Integrating Team Game Tournament by Using Digital Based Application to Enhance Students' Writing Skill at Seventh Grade in Junior High School - Agung Safrianto; Abdul Rosyid; Purwati; Febriyana Khoirulnisa; Mutiara Putri A; Wilda Khoirunnisa (Universitas Islam Negeri Palopo, 2025)
This study aims to improve the writing skills of seventh-grade students at Junior High School 5 Bogor through the implementation of the digital-based Team Game Tournament (TGT) strategy. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection, conducted over two cycles. Data were collected through writing tests (pre-tests and post-tests), observation sheets, field notes, and student questionnaires. Quantitative results showed improvement in students' writing scores, from an average of 52.40 in the pre-test to 75.40 in the post-test of Cycle II. Qualitative findings revealed increased student motivation, participation, and collaboration in writing activities. The study concludes that integrating TGT with digital applications is effective in improving students’ writing skills and active engagement in the classroom. This finding demonstrates that the integration of technology into collaborative learning significantly enhances student engagement and achievement in writing.